Role of intrinsic motivation in the process of mastering the piano (Per Musi, 2022)
The article presents the results of a study aimed at analyzing the role of intrinsic motivation in the process of mastering the piano. The study used various methods to identify the facts of the influence of intrinsic motivation on the process of mastering the piano for students of music educational institutions and for people who chose a different path in further education. The study revealed a number of interesting facts that will help to look at the problem of motivation in the context of internal motives for mastering such a musical instrument as the piano.